The measure of international law : effectiveness, fairness and validity : proceedings of the 31st Annual Conference of the Canadian Council on International Law, Ottawa, October 24-26, 2002 /: effectiveness, fairness and validity : proceedings of the 31st Annual Conference of the Canadian Council on International Law, Ottawa, October 24-26, 2002. (2004) - Unknown
No abstract available